Turismo: evoluzione tecnologica e paradigmi interpretativi - Gilli, Monica (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
While the consequences that the introduction of new technologies has had on tourism practice are well known, the problem of the consequences that this technological evolution in tourism has on the explanatory-interpretative capacities of some paradigms of the sociology of tourism is much less explored in literature. In this paper we will try to show, with particular reference to two classic paradigms, - tourism as a "rite of passage" and as a "search for authenticity", as a series of important cultural transformations that accompanied the advent of such technologies force a redeﬁnition, or at least a greater caution, in the use of such models.